Organizational and Legal Aspects of Independent Assessment of Qualification - Victor A. Lebedev; Elena I. Lebedeva (Учёт. Анализ. Аудит, 2019)
Topic. Practical application of the Federal Law “On the independent evaluation of qualifications” in force since January 1, 2017. Purpose. Analysis of independent assessment of qualifications of employees, types and forms of independent evaluation, assessment tools, ways of confirming professional experience during the qualifying exam. Methodology. The research is based on dialectic approach. The system method is used to research the current legislation and law-enforcement practice in branches of economy. Results. Along with the procedure of personnel certification within the organization, the system of qualification independent assessment provides the head of this organization with an opportunity to objectively estimate if the qualification of workers complies with to requirements set in a standard. The obvious ultimate goal of independent assessment of qualification of workers is the increase in overall performance of the whole organization. Such procedure also motivates staff to improve their professional skills. Conclusions. The authors offer to specify a legal form of the center for qualification evaluation by a Federal Act, to establish requirements to the members of this organization and the criteria of independence of qualification assessment; to specify the legislator’s initiatives, in particular, concerning a legal form and requirements to staff of the estimated centers.